Effect of electrode annealing to the performance of novel 3D-printed floating microbial fuel cell for polluted surface water remediation - Paclibar, Arnil Jr. B.; Pamintuan, Kristopher Ray S. (International Journal of Renewable Energy Development, 2025)
Microbial fuel cells (MFCs) produce electricity by harnessing the electrons generated from the biochemical reactions of bacteria in wastewater. In this study, the performance of a novel 3D-printed floating microbial fuel cell (MFC) design was investigated. The design utilized protopasta conductive polylactic acid (PLA) for the electrodes and ESUN non-conductive PLA+ for the separator. The electrodes were annealed, and its effects on the electrodes' resistances and peak proton transfer rate were investigated. After annealing both electrodes, the resistance and peak proton transfer values dropped. The average current and voltage generation were also examined, and the results showed that the annealed set showed lower values of both voltage and current compared to the non-annealed set. Stacking studies were also done, and the configuration that exhibited the largest power and power density was 8P for both annealed and non-annealed sets. The maximum power density obtained by the non-annealed design is 7.195 µW/m2, 21.81 µW/m2, and 26.74 µW/m2 for IND, 3S4P, and 4P3S, respectively. For the annealed set, the maximum power densities are 1.059 µW/m2, 24.03 µW/m2, and 24.09 µW/m2 for IND, 3S4P, and 4P3S, respectively. Lastly, the COD reduction efficiency of the design is 78.57% and 79.17% for the non-annealed and annealed sets, respectively. The results of this study prove that 3D-printing technology can be a possible option for the manufacturing and improvement of future MFC studies. The study verified that annealing reduced the performance of the MFC mainly because of the design where its electrodes are also acting as the chambers.